DNA repair in the archaea – an emerging picture - White, Malcolm F.; Allers, Thorsten (Oxford University Press, 2018)
There has long been a fascination in the DNA Repair pathways of archaea, for two main reasons. Firstly, many archaea inhabit extreme environments where the rate of physical damage to DNA is accelerated. These archaea might reasonably be expected to have particularly robust or novel DNA repair pathways to cope with this. Secondly, the archaea have long been understood to be a lineage distinct from the bacteria, and to share a close relationship with the eukarya, particularly in their information processing systems. Recent discoveries suggest the eukarya arose from within the archaeal domain, and in particular from lineages related to the TACK superphylum and Lokiarchaea. Thus, archaeal DNA repair proteins and pathways can represent a useful model system. This review focuses on recent advances in our understanding of archaeal DNA repair processes including Base Excision Repair (BER), Nucleotide Excision Repair (NER), Mismatch Repair (MMR) and Double Strand Break Repair (DSBR). These advances are discussed in the context of the emerging picture of the evolution and relationship of the three domains of life.